Protein-RNA interactions in the U5 snRNP of Saccharomyces cerevisiae. - Dix, I (1998)
We present here the first insights into the organization of proteins on the RNA in the U5 snRNP of Saccharomyces cerevisiae. Photo-crosslinking with uniformly labeled U5 RNA in snRNPs reconstituted in vitro revealed five contacting proteins, Prp8p, Snu114p, p30, p16, and p10, contact by the three smaller proteins requiring an intact Sm site. Site-specific crosslinking showed that Snu114p contacts the 5' side of internal loop 1, whereas Prp8p interacts with five different regions of the 5' stem-loop, but not with the Sm site or 3' stem-loop. Both internal loops in the 5' domain are essential for Prp8p to associate with the snRNP, but the conserved loop 1 is not, although this is the region to which Prp8p crosslinks most strongly. The extensive contacts between Prp8p and the 5' stem-loop of U5 RNA support the hypothesis that, in spliceosomes, Prp8p stabilizes loop 1-exon interactions. Moreover, data showing that Prp8p contacts the exons even in the absence of loop 1 indicate that Prp8p may be the principal anchoring factor for exons in the spliceosome. This and the close proximity of the spliceosomal translocase, Snu114p, to U5 loop 1 and Prp8p support and extend the proposal that Snu114p mimics U5 loop 1 during a translocation event in the spliceosome.